1986
DOI: 10.1007/bf01314147
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interferon on Vero cells persistently infected with SSPE virus and lytically infected with measles virus

Abstract: The effect of lymphoblastoid interferon (IFN) on viral polypeptides synthesized in a Vero cell culture persistently infected with subacute sclerosing panencephalitis virus (SSPE-Vero) was compared to that of Vero cells infected with exogenous measles virus. After IFN treatment there was no significant decrease in the synthesis of SSPE viral proteins, but inhibition of synthesis of measles polypeptides was readily seen. In Vero and SSPE-Vero cells IFN was able to inhibit replication of Sindbis virus although th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1988
1988
1995
1995

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
(6 reference statements)
0
6
0
Order By: Relevance
“…Endogenous IFN production by these persistently infected cells has been shown to be low or absent [20,30,14]. We have shown previously that Vero cells persistently infected with SSPE virus are significantly less susceptible to the antiviral action of IFN when compared to uninfected Vero cells [6]. A change in the susceptibility to the antiviral and antiproliferative actions of IFN of cells persistently infected with Sendai virus has also been previously reported [11][12][13].…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…Endogenous IFN production by these persistently infected cells has been shown to be low or absent [20,30,14]. We have shown previously that Vero cells persistently infected with SSPE virus are significantly less susceptible to the antiviral action of IFN when compared to uninfected Vero cells [6]. A change in the susceptibility to the antiviral and antiproliferative actions of IFN of cells persistently infected with Sendai virus has also been previously reported [11][12][13].…”
Section: Introductionmentioning
confidence: 72%
“…Incorporation of 3H-leucine was inhibited by 78% in Vero cells and 65% in Sendai-Vero cells when the cells were exposed to a concentration of 10-6M of 2-5A. Previously we have shown that SSPEVero cells reacted to 2-5A in a similar manner with significant inhibition of 3H-leucine incorporation [6]. .…”
Section: Sensitivity Of Sendai-vero Cells To 2-5amentioning
confidence: 77%
See 2 more Smart Citations
“…The kinase inhibitors produced by virus infection are already defined in cells infected with adenovirus, vaccinia virus and reovirus (Whitaker-Dowling & Youngner, 1983;Palz & Esteban, 1984;Rice & Kerr, 1984;Schneider & Shenk, 1987;Imani & Jacobs, 1988). On the other hand, Crespi et al (1986) reported that Vero cells persistently infected with Sendai and subacute sclerosing panencephalitis (SSPE) viruses acquired a resistance to IFN because of the reduced induction of 2-5AS in spite of the normal level of IFN receptor. It has been also reported that failure to induce 2-5AS activity was observed in K562 cells persistently infected with measles and mumps viruses, and BALB3T3 cells persistently infected with Moloney murine leukaemia virus.…”
mentioning
confidence: 99%